Uterine fibroids increase the risk of hypertensive disorders of pregnancy: a prospective cohort study. Issue 5 (4th May 2021) - Chen, Yequn; Lin, Mengyue; Guo, Pi; Xiao, Jiaxin; Huang, Xiru; Xu, Lan; Xiong, Nianling; O'Gara, Mary Clare; O'Meara, Michael; Tan, Xuerui
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: It is unclear whether uterine fibroids are associated with the occurrence of hypertensive disorders of pregnancy (HDP). Thus, this study aimed to evaluate the association between uterine fibroids and HDP in a prospective cohort. Methods: Overall, 2404 pregnant women who received antenatal care were enrolled in a prospective cohort in China between 2014 and 2016; 2277 women met the inclusion criteria of this study. The clinical characteristics of participants were assessed via questionnaires and physical examinations at baseline (before the 20th week of gestation), 21st–27th, 28th–34th, and 35th–39th gestational weeks. Ultrasound examination was performed before the 20th week of pregnancy to determine the presence of uterine fibroids. Linear mixed-effect and Cox proportional hazard regression models were used to analyze the association of uterine fibroids with blood pressure and HDP. Results: Of 2277 pregnant women, 242 (10.6%) had uterine fibroids, and 45 (2.0%) subsequently developed HDP. The incidence of HDP in women with and without uterine fibroids was 5% ( n = 12) and 1.6% ( n = 33), respectively. The longitudinal SBPs and DBPs were significantly higher in women with uterine fibroids than in those without. The multivariable Cox model showed that the presence of uterine fibroids was associated with increased HDP risk (adjusted hazard radio: 2.95, 95% confidence interval: 1.35–6.44). Conclusion: Uterine fibroids in early pregnancy were associated with an increased HDP risk. Blood pressure of women with uterine fibroids should be closely monitored, and HDP preventive measures are crucial.